Analysis of the Relationship Between Information Technology, Integrated Management Information Systems, and Employee Performance at STTN Lampung - Ferdiansyah, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Information Technology (IT) and Integrated Management Information System (IMIS) are powerful tools for enhancing employee performance within an institution, necessitating research in this area. This study aims to achieve three primary objectives: 1) to identify the influence of Information Technology on STTN Lampung, 2) to assess the impact of IMIS on the performance of STTN Lampung staff, and 3) to determine the combined effect of IT and IMIS implementation on overall employee performance at STTN Lampung. The research was conducted at STTN Lampung and involved employees proficient in computer operations and knowledgeable in IT. Additionally, the study focused on three main variables: IT, IMIS, and employee performance. Primary data were collected through questionnaires from 84 respondents, selected using the Slovin formula and purposive sampling technique. The analysis revealed positive and significant effects of both IT and IMIS on employee performance at STTN Lampung